'I'm having a baby not a labour': Sense of coherence and women's attitudes towards labour and birth. (December 2019) - Ferguson, Sally; Davis, Deborah
Abstract: Objective: In Western countries, caesarean section rates are increasing and spontaneous vaginal birth rates are decreasing at a rapid rate. This trend has implications for childbearing women's health and calls into question the use of pathogenesis to frame maternity services. The theory and practice of salutogenesis offers a viable alternative as it emphasises health rather than illness. Sense of coherence and generalized resistant resources (GRRs) are the cornerstones of salutogenesis and sense of coherence is a predictive indicator of health. As strong sense of coherence in pregnant women is associated with half the likelihood of caesarean section compared to women with weak sense of coherence, the objective of this study is to examine the association between sense of coherence and women's attitude towards their birthing experiences. Design, setting and participants: This paper reports on the qualitative component only of a longitudinal study where 753 women planning to have their babies in an Australian tertiary maternity service, completed questionnaires in pregnancy and postnatally. Women answered one openended question during the pregnancy and one open-ended question approximately eight weeks postnatally. Data were analysed by qualitative content analysis. Findings: When the open-text responses of 119 women with strong sense of coherence and 177 women with weak sense of coherence were analysed, the categories of Language, Demeanour and Focus were identified. Women with strong sense of coherence have a positive, relaxed and baby-focused attitude. In salutogenic terms this attitude towards labour and birth can be described as increased comprehensibility, increased manageability, decreased meaningfulness in the experience of giving birth, increased internal GRRs and increased external GRRs. Women with weak sense of coherence have a more negative, worried and labour-focused attitude. In salutogenic terms this attitude towards labour and birth can be described as decreased comprehensibility, decreased manageability, increased meaningfulness in the experience of giving birth, decreased internal GRRs and decreased external GRRs. Key conclusion: Strong sense of coherence in childbearing women is expressed through a positive, relaxed and baby-focused attitude while weak sense of coherence is expressed through negative, worried and labour-focused attitude in childbearing women towards labour and birth. Implications for practice: As sense of coherence is a modifiable predictor of health, application of the study findings could focus on midwifery work including antenatal education that aims to decrease caesarean section rates by strengthening women's sense of coherence in pregnancy.